Molecular characterisation of eggplant and related species: stability analysis for yield and reaction to bacterial wilt under the humid subtropics of North Eastern India. Issue 6 (2nd November 2019) - Verma, Veerendra Kumar; Pandey, Avinash; Baiswar, Pankaj; Jha, Anjani Kumar
ABSTRACT: Eggplant ( Solanum melongena L.) is an important solanaceous vegetable crop grown worldwide over tropics and subtropics. Bacterial wilt (caused by Ralstonia solanacearum ) is one of the most serious diseases of the crop, especially in the humid tropics. The present investigation was carried out using 26 accessions of eggplant including wild relatives aiming to identify stable genotypes of eggplant with tolerant to bacterial wilt. The accessions were characterised using 40 simple sequence repeat (SSR) markers. Thirty-four markers were found polymorphic and produced 136 alleles with an average of four alleles per marker. All the markers have shown amplification across accessions of eggplant-related species. Markers EES-050, EES-065, and EES-066 were highly informative. Among the species, scarlet eggplant ( Solanum aethiopicum var.gilo ) was found to be the closest to S. melongena . Markers, EES-031 and EES-051, were specific to the accessions with tolerance to bacterial wilt. Based on the three-year evaluations, the disease incidence (DI) ranged from 1.27% ( S. torvum ) to 72.85% ( S. melongena var. Kasi Taru). The AMMI and GGE biplot analyses have shown the significant contribution of genotype variation over the environment and interaction. The local eggplant accessions (Bhola Nath, RCMB-10, Singh Nath and RCMBL-1) were found highly stable for yield with lowest wilt incidences when compared to other Indian accessions. The results suggested the incorporation of local accessions/landraces into the eggplant breeding programmes aiming to develop stable cultivars with improved yield and resistant to bacterial wilt. Abbreviation: AMMI, Additive Main-Effects and Multiplicative Interaction; GGE, Genotype Main Effect plus Genotype-by-Environment Interaction; SSRs, Simple Sequence Repeats; QTLs, Quantitative Trait Loci; AMOVA, Analysis of Molecular Variance;